Theoretical foundations that support the teaching of microbiology in the formation of general doctors - Lilianne Dominguez Céspedes; Raysa Hernández Batista; Roberto Pérez Almaguer (Zien Journals, 2024)
The University is par excellence, the social institution with the greatest capacity to preserve, develop and disseminate culture in its broadest sense. Therefore, it is to be expected that it puts the most advanced knowledge at the service and safeguard of humanity. The research addresses the theoretical foundations that support the teaching of microbiology in higher medical education, which is its objective. Method: The discipline of microbiology in the training of the general practitioner is characterized as a synthesis of a preparation that allows the graduate to promote theoretical and practical skills around the microbiological content in the training of the general practitioner. Findings: The contents of the discipline and subject of Medical Microbiology have been published through the different study plans, and their contents are interrelated with the different subjects contained in the medical degree program. Implications for research and practice: However, we must deepen the treatment of practical microbiological skills during the development of the subject and thus achieve a health professional prepared to respond to the needs of society.
Keywords: Teaching; microbiology; formation; doctor